Association of Tooth Loss with New-Onset Parkinson’s Disease: A Nationwide Population-Based Cohort Study - Ho Geol Woo; Yoonkyung Chang; Ji Sung Lee; Tae-Jin Song (Parkinson's Disease)
Introduction. Tooth loss is associated with poor oral hygiene. During insufficient oral sanitation, focal infection and inflammation can occur and these reactions may induce systemic inflammation. Systemic inflammatory reaction may be related to the degeneration of dopamine neurons in the substantia nigra. We hypothesized that tooth loss is related to increased risk of new-onset Parkinson’s disease. Methods. Between 2003 and 2006, we included 153,165 participants from the national health insurance system-health screening cohort in Korea. The incidence of new-onset Parkinson’s disease was defined as International Classification of Diseases-10 code “G20,” accompanying the prescription records for any anti-Parkinson’s disease medication. Results. Approximately 19.9% of the included participants had periodontal disease. After a median duration of 10.4 years, 1,227 (0.8%) cases of new-onset Parkinson’s disease were noted. The number of tooth loss was positively related to an increased risk of new-onset Parkinson’s disease. Contrastingly, the frequency of tooth brushings and dental clinic visits for any causes as well as competent dental care were negatively related to the development of new-onset Parkinson’s disease. In multivariable analysis, the number of tooth loss (≥15) was positively related to new-onset Parkinson’s disease development (hazard ratio: 1.38, 95% confidence interval (1.03–1.85), p=0.029, p for trend = 0.043) after adjusting variables. Conclusion. Our study demonstrated that the number of tooth loss was positively correlated with a higher risk of new-onset Parkinson’s disease development in a longitudinal study setting. Increased number of tooth loss may be an important risk indicator of new-onset Parkinson’s disease.